Amniopatch as an active treatment of spontaneous previable rupture of membranes. (12th December 2022) - Ferianec, Vladimír; Križko, Marián; Gábor, Martin; Papcun, Peter; Alföldi, Martin; Feriancová, Michaela
Abstract: Objective: To assess the use of amniopatch – intraamniotic application of maternal platelets and cryoprecipitate, in patients after spontaneous previable rupture of membranes (sPPPROM) in terms of its effect on the course and outcome of pregnancy in the largest cohort so far. Since the amniopatch is currently used only to treat patients with iatrogenic preterm rupture of membranes, aim of this study was to find out, if amniopatch could be also used in case of sPPPROM as a safe alternative to currently used expectant management and to compare the results with published data on expectant management. Methods: The study included 53 patients with single-fetal pregnancy after sPPPROM who underwent amniopatch as an experimental method in the years 2008–2019. Authors evaluated individual characteristics for the whole group as well as a subgroup of live-born neonates who survived to discharge and abortions/live-born infants who did not survive to discharge. Results: The mean time of sPPPROM was 19 + 3 gestational week (gw) and of amniopatch performance 22 + 0 gw. Across the group, the miscarriage rate was 33.96%, survival rate 66.03%, mortality rate after delivery 8.57%, survival rate to discharge 60.37%. The mean time of latency period was 5 + 3 gw in the total group, 7 + 1 gw in the group of live births who survived to discharge. We did not find any maternal/fetal complications related directly to amniopatch procedure. Conclusion: Amniopatch is a safe treatment alternative in patients with sPPPROM who require an active approach. It is associated with high percentage of a success rate in terms of duration of pregnancy and neonatal survival. In order to elucidate the possible mechanism of amniopatch effect in sPPPROM despite failure of complete sealing of membrane defect, authors give novel hypothesis of antimicrobial effect of amniopatch based on literature data.